The constitutional conflictology in the system of constitutional science - Irina A. Tretyak (Правоприменение)
The subject. The article is devoted to process of constitutional conflictology theory formation as separate field of constitutional science, researching constitutional conflicts and different measures for their prevention and solving.The purpose of the article is to define theoretical base for constitutional conflictology theory formation.The methodology of the study includes general scientific methods (analysis, synthesis, description) and sociological approach. The main results and scope of their application. The author describes the genesis of constitutional conflictology theory, its subject, methodology and system. The author substantiates necessity of application of theoretical and methodological bases of conflictology’s science in the constitutional and municipal law for the purpose of forecasting, identification and the resolution of the corresponding constitutional conflicts.Causes of constitutional conflictology theory formation are:- accumulation of results of many constitutional researches of different aspects of legal conflict and its expression in constitutional law;- public power as an object of constitutional relationships and as main cause of conflict situation in society;- character and scale of constitutional conflict’s aftermaths;- conflictolgy nature of the Constitution of Russian Federation.Constitutional conflictology is a research level of legal conflictology exploring constitutional conflict, its causes and methods of prevention and solving, and also constitutional and municipal legal norms with conflictology nature.A methodology of constitutional conflictology is symbiotic also and contains three different groups of methods:I group of general scientific methods (dialectical, system, functional);II group of different scientific methods (historical, logical, statistic);III group of special methods: legal methods (formal-legal methods, method of a prediction of legal consequences, comparative method), a generic definition description method.A system of constitutional conflictology consists four interconnected elements:1)                 theory of constitutional conflict;2)                 methods of prevention and solving constitutional conflicts;3)                 constitutional and municipal legal norms with conflictology nature;4)                 different types of constitutional conflicts and methods of their solving.Conclusions. Constitutional conflictology theory has been formating in constitution legal science as a separate field exploring constitutional conflict and all of its aspects.